2022
DOI: 10.3389/fchem.2022.908312
|View full text |Cite
|
Sign up to set email alerts
|

ADSCs Promote Tenocyte Proliferation by Reducing the Methylation Level of lncRNA Morf4l1 in Tendon Injury

Abstract: Objective: Tendons are the special connective tissue that connects bones to muscles and governs joint movement in response to loads passed by muscles. The healing of tendon injuries is still a challenge. In recent years, adipose-derived mesenchymal stem cells (ADSCs) have been increasingly used for tissue regeneration, but the underlying mechanism of tendon injury still remains unclear.Methods: High-throughput sequencing was used to identify a novel lncRNA, whose expression was significantly decreased in injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In contrast to this study, the use of miR-378a knock-in transgenic mice showed that the absence of this molecule inhibited collagen and ECM production, tendon differentiation and tendon repair in vitro and in vivo [143]. A study showed that methylation of the promoter of the long non-coding RNA (lncRNA) Morf4l1 in damaged tendons led to a decrease in its expression and inhibition of tenocyte proliferation [144]. This molecule stimulated TGF-β2 via miR-145-5p.…”
Section: Genetic Modificationmentioning
confidence: 57%
“…In contrast to this study, the use of miR-378a knock-in transgenic mice showed that the absence of this molecule inhibited collagen and ECM production, tendon differentiation and tendon repair in vitro and in vivo [143]. A study showed that methylation of the promoter of the long non-coding RNA (lncRNA) Morf4l1 in damaged tendons led to a decrease in its expression and inhibition of tenocyte proliferation [144]. This molecule stimulated TGF-β2 via miR-145-5p.…”
Section: Genetic Modificationmentioning
confidence: 57%
“…It was reported that tendon cell oxidative stress levels were reduced and cell proliferation was enhanced after lncRNA demethylation, suggesting that lncRNA demethylation rescued tendon injury. In addition, they found that adipose-derived MSCs promoted healing after tendon injury by reducing the promoter methylation level of lncRNA Morf4l1 ( Zhao et al, 2022 ). Targeting the lncRNA dnm3os repressed a range of genes associated with fibrogenesis ( Zheng et al, 2018 ).…”
Section: Long-stranded Non-coding Rna and Tendon Injurymentioning
confidence: 99%
“…251 In a related study, Zhao et al co-cultured ADSCs with injured tenocytes for 48 h, ADSCs clearly promoted proliferation rates and largely reduced levels of oxidative stress in the injured tenocytes via inhibition of methylation LncRNA Morf4l1. 252 Therefore, it is hypothesized that ADSCs mainly target the regeneration of Zone I in the injured enthesis tissue, and exert their positive effect through LncRNA Morf4l1 demethylation.…”
Section: Tissue Engineering Strategies For Enthesis Reconstructionmentioning
confidence: 99%